Epistemic in/justice: Towards 'Other' ways of knowing. (June 2022) - Hutton, Martina; Cappellini, Benedetta
This paper brings a critical awareness to the interrelations between epistemic injustice and knowledge hierarchies, through an insufficient attention to the Other as epistemically harmed. Because of the dominant empirical and theoretical authority Others are subjected to in research practices and dissemination, our paper explores how marginalised voices possess less epistemic agency due to their disciplining, neglect and subjugation as knowers through testimonial and hermeneutical injustice. We contribute two new categories of epistemic injustice in marketing; Silencing and Ignorance; areas, which reproduce and reify knowledge hierarchies but equally provide scholars with an opportunity to contest epistemic dominance. Through an explicit acknowledgement of the relationship between difference, power and knowledge in meaning-making, we argue for Other consciousness which entails (i) privileging Othered knowledge, (ii) highlighting structural epistemic in/justice within Marketing academe and (iii) advocating for artistic-inclusive processes, to alter how we theorise knowing Others, and Other knowers, in marketing scholarship.